Efektivitas Polisi Rukun Warga Di Kecamatan Marawola Kabupaten Sigi - Kariyasa, I Wayan; Mustainah; Asrifai (Transgenera: Jurnal Sosial, Politik dan Humaniora, 2025)
This research aims to analyze the effectiveness of the Rukun Warga Police (RW Police) in Marawola District, Sigi Regency. The RW Police is an extension of the police in the neighborhood security system formed based on the Regulation of the Chief of the National Police of the Republic of Indonesia Number 4 of 2020 concerning Swakarsa Security. This research uses a qualitative approach with the Eugene Bardach model of policy analysis which consists of eight aspects, namely defining the problem, collecting evidence, constructing alternatives, selecting criteria, projecting outcomes, facing trade-offs, deciding, and telling stories. Data collection was carried out through in-depth interviews with key informants including the Marawola Police Chief, Head of Binmas Sub-District, Rukun Warga Police (RW Police), the implementation of the Rukun Warga Police (RW Police) policy in Marawola Sub-District shows a fairly good level of effectiveness, reflected in the success in handling security cases at the RW level and increasing the sense of security of the community. However, there are several obstacles that affect the effectiveness of the program, namely limited operational budget, non-standardized reporting system, and uneven distribution of personnel.